The left ventricular assist device as a patient monitoring system - Moscato, Francesco; Gross, Christoph; Maw, Martin; Schlöglhofer, Thomas; Granegger, Marcus; Zimpfer, Daniel; Schima, Heinrich (Annals of Cardiothoracic Surgery; Vol 10, No 2 (March 31, 2021): Continuous-Flow MCS in End-Stage Heart Failure I, 2021)
Technological progress of left ventricular assist devices (LVADs) towards rotary blood pumps and the optimization of medical management contributed to the significant improvements in patient survival as well as LVAD support duration. Even though LVAD therapy is now well-established for end-stage heart failure patients, the long-term occurrence of adverse events (AE) such as bleeding, infection or stroke, still represent a relevant burden. An early detection of AE, before onset of major symptoms, can lead to further optimization of patient treatment and thus mitigate the burden of AE. Continuous patient monitoring facilitates identification of pathophysiological states and allows anticipation of AE to improve patient management. In this paper, methods, algorithms and possibilities for continuous patient monitoring based on LVAD data are reviewed. While experience with continuous LVAD monitoring is currently limited to a few centers worldwide, the pace of developments in this field is fast and we expect these technologies to have a global impact on the well-being of LVAD patients.